The relation of familial longevity and progression of disability in multiple sclerosis - Gao, Xin (2019)
Background: Multiple sclerosis (MS) is an immune-mediated demyelinating disease with immune system attacking the protective myelin sheath that covers nerve fibres and causes neurological deficits. Ageing is a factor that is related to the progression of disease disability. Previous studies have shown an inheritance of longevity. The genetic or familial effect on disability progression in MS has not been studied in detail previously.